Effects of Logo Design toward Brand Personality Perception: A Study of Logo Elements in Real Estate Business - Mittheera Leelayudthyothin (My University, 2022)
The topics of logo design perceptions have been examined among academic scholars recently. However, elements of logo as one aspect of logo designs were rarely studied and required to be investigated. This research aimed to measure the effects of logo elements comprising type font, graphic form, and color toward brand personality perceptions, as well as to explore the relationship between business stakeholders and brand personality. In addition, logo design meaning and brand personality traits including sincerity, excitement, security, and up to date were evaluated toward logo elements. Two hundred and sixty-five samples were selected using convenience sampling from employees and residents of Thai property developers. The mix method approach was employed for the data collecting through interviewing and questionnaire survey and analyzed by Chi-square tests. The findings reveal that logo design transfers all-inclusive meaning to viewers, encompassing name, graphic, and color interpretation. Besides, there is a connection between logo elements and perception of brand personality, but in order to obtain one salient dimension of brand personality, exhibiting the whole logo was suggested rather than individual element of logo. Furthermore, brand personality was considered vital among market sharing property industry which personality of sincerity was chiefly perceived when stakeholders appreciate a logo of their real estate brands.
Keywords: Logo (programming language); Sincerity; Consumer Behavior in Brand Consumption and Identification